STUDIED ON AN IMPROVED CONSTITUTIVE MODEL AND SIMULATION FOR MILLING MEDICAL Ti-xNb-2Fe ALLOY - JIANG XiaoHui; LI ShengChao; LI Qiang (Jixie qiangdu)
At present,medical Ti-xNb-2Fe alloy is widely used,but it still needs follow-up finishing in order to obtain high precision surface quality. The simulation process of Ti-xNb-2Fe alloy was established,a modified Johnson Cook（ J-C）constitutive model considering the effects of strain,strain rate and temperature on flow stress was constructed. And a cutting physical parameters prediction method based on medical Ti-xNb-2Fe alloy was proposed in this work. First,the physical properties calculation software JMatPro was used to obtain the basic data of stress-strain curve of Ti-xNb-2Fe alloy during phase transformation,and the modified J-C model parameters were fitted by variable separation method. Then,on the platform of Advant Edge FEM finite element software,the flow stress model including phase transition was input into the software system through Fortran compiler. Finally,the data results of cutting force,cutting temperature and surface roughness simulated by J-C model and modified J-C model were compared with the physical testing results. The results indicated that the constitutive equation parameter A value and Bvalue decrease by 21% and 27% with the increase of trace element Nb content,respectively. The average percentage errors of cutting force,cutting temperature,surface roughness and physical testing results of finite element simulation using modified model were less than 25%,19% and 30%,respectively. The model can provide the optimization of process parameters for the follow-up finishing of medical Ti-xNb-2Fe alloy.